A STUDY ON PRANAVAHA SROTAS AND ITS MULASTHANA (AYUSHDHARA, 2016)
Human body is said to be made up of Srotas. The unvitiated state of Srotas is the material cause for diseases to not affect the body and for maintaining healthy state of the body. Hence the Ayurvediya clinical foundation is based on thorough knowledge of these Srotas. Right from birth to death Swasuchhavasa Kriya is one of the utmost sign of life. The Shwasa Kriya is one of the main functions of PranaVata. Pranavaha Srotas means the channel, which carries the external air into the body to sustain the life. Thus the Pranavaha Srotas is most important for maintaining life and longevity. Hridaya and Mahasrotas are the Mula Sthana of Pranavaha Srotas. The diseases like Shwasaand Hikka have their origin from the Mulasthana of Srotas. The Mulasthana of Srotas is important area for proper functioning of Srotas. Hence the treatment of any disease should also include intervention for the betterment of Srotas. It implies the necessity of a thorough knowledge of Srotas, its Mulasthana, its normal functioning etc. In this respect here an effort is made to thoroughly understand the Pranavaha Srotas, its Mula Sthana and Shawashan Prakriya etc.